Central Retinal Vein Occlusion Presumably Associated with Lupus Anticoagulant Induced by SARSCoV-2. (17th November 2022) - Cuadros Sánchez, Carlos; Egüen, Cristina Sacristán; Gutierrez-Ezquerro, Raquel; Giralt-Peret, Lena; Fonollosa, Alex
ABSTRACT: Purpose: To report a case of unilateral central retinal vein occlusion (CRVO) and macular edema presumably associated with lupus anticoagulant (LA) induced by severe acute respiratory syndrome coronavirus 2 (SARS CoV-2). Method: Case report. Results: A 32-year-old male patient presented to the emergency department with a 5-day history of blurry vision. He was diagnosed with a CRVO and macular edema. The only pathological finding was positive LA which could have been induced by his recent confirmed SARS CoV-2 infection. The patient's evolution was satisfactory after two injections of Intravitreal dexamethasone (Ozurdex®), with improvement in macular edema and visual acuity. Conclusion: COVID-19 may be associated to retinal vascular occlusive disorders. Transient virus-induced LA might play a role in the pathogenesis of the thrombotic event.